2014
DOI: 10.11144/javeriana.upsy13-2.tcps
|View full text |Cite
|
Sign up to set email alerts
|

Text comprehension as a problem solving situation

Abstract: Research in text comprehension has provided details as to how text features and cognitive processes interact in order to build comprehension and generate meaning. However, there is no explicit link between the cognitive processes deployed during text comprehension and their place in higher-order cognition, as in problem solving. The purpose of this paper is to propose a cognitive model in which text comprehension is made analogous to a problem solving situation and that relies on current research on well-known… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 111 publications
0
2
0
1
Order By: Relevance
“…In order to interpret the findings in terms of current theories, we propose a modified version of the 'shared circuits' model in which specific cognitive systems are necessary for processing of information. Specifically, we adopt a neurocognitive model that accounts for the processing of visual [42] and linguistic information [64][65][66] and that highlights the use of inference memory and simulation systems as essential to any cognitive process. More importantly, this model predicts that sensorimotor systems are required during dynamic interactions between vision and language, and recent behavioral [67] and imaging [68] evidence supports these predictions.…”
Section: Discussionmentioning
confidence: 99%
“…In order to interpret the findings in terms of current theories, we propose a modified version of the 'shared circuits' model in which specific cognitive systems are necessary for processing of information. Specifically, we adopt a neurocognitive model that accounts for the processing of visual [42] and linguistic information [64][65][66] and that highlights the use of inference memory and simulation systems as essential to any cognitive process. More importantly, this model predicts that sensorimotor systems are required during dynamic interactions between vision and language, and recent behavioral [67] and imaging [68] evidence supports these predictions.…”
Section: Discussionmentioning
confidence: 99%
“…Also, research has shown that narrative texts enable rich mental representations that encapsulate the gist of a narrative’s topic [ 52 ]. In a nutshell, scientific evidence has indicated that narratives are the most optimal discursive tool to retain the gist of any message in memory, elicit emotional responses, and promote social cognition [ 45 , 52 , 54 , 55 , 56 ]. 11 Narratives thus aid in the goal of collectively constructing representations of reality and charge them with meaning [ 10 ].…”
Section: Narratives and Nb: Psychological Basis And Social Role In Pu...mentioning
confidence: 99%
“…Okuduğunu anlama sürecinde, okur kaynaklı ve metin kaynaklı duygular etkileşime girmektedir (Marmolejo-Ramos ve Cevasco, 2014). Öncelikle okurun ruh hâli, metni anlama düzeyini etkilemektedir (Bohn-Gettler ve Rapp, 2011).…”
Section: Okuduğunu Anlama Sürecinde Duygularunclassified